2017
DOI: 10.1039/c7ra07239b
|View full text |Cite
|
Sign up to set email alerts
|

Upgrading of palmitic acid over MOF catalysts in supercritical fluid of n-hexane

Abstract: The addition of phosphotungstic acid (PTA) to the synthesis mixture of PdCu@FeIII–MOF-5 yields the direct encapsulation of PTA inside the MOF structure (i.e. PTA@PdCu@FeIII–MOF-5) through a facile solvothermal approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 53 publications
(77 reference statements)
1
17
0
1
Order By: Relevance
“…Hence, algae bio-oil cannot be used as transportation fuel without removing these fatty acids. For this, Fang et al 262 developed a facile one-pot strategy to convert palmitic acid into hexadecane over a bifunctional MOF catalyst, consisting of encapsulated phosphotungstic acid inside the MOF structure of PdCu@Fe III -MOF-5. The developed catalyst shows an improved acidity and completely converts palmitic acid with a high selectivity to hexadecane.…”
Section: Bifunctionalised Mofsmentioning
confidence: 99%
“…Hence, algae bio-oil cannot be used as transportation fuel without removing these fatty acids. For this, Fang et al 262 developed a facile one-pot strategy to convert palmitic acid into hexadecane over a bifunctional MOF catalyst, consisting of encapsulated phosphotungstic acid inside the MOF structure of PdCu@Fe III -MOF-5. The developed catalyst shows an improved acidity and completely converts palmitic acid with a high selectivity to hexadecane.…”
Section: Bifunctionalised Mofsmentioning
confidence: 99%
“…For example, Wang and co‐workers developed a surface‐energy–driven approach by using PVP to synthesize a series of well‐defined hollow MOF (e.g., MOF‐5, MOF‐5(FeII), and MOF‐5(FeIII)) nanocages. [10b] Wu and co‐workers further followed Wang’s method to encapsulate phosphotungstic acid inside MOFs . Lei and co‐workers synthesized hollow ZIF‐8 structures with the assistance of sodium dodecyl sulfate …”
Section: Preparation Of Hollow Mof Micro/nanostructures and Their Dermentioning
confidence: 99%
“…[10b] They found that such hollow structures had better activity than PdCu dendrites, because the hydrogenation reaction was accelerated in the hollow nanoreactors. Analogously, hollow phosphotungstic acid (PTA)@CdCu@MOF‐5(FeIII) yolk–shell nanostructures showed good selective hydrogenation performance toward palmitic acid . Except for the activity, the MOFs nanoreactors exhibit a considerable effect on the catalytic selectivity.…”
Section: Applicationsmentioning
confidence: 99%
“…Advances in Polymer Technology e presence of oxygen-containing C16-C18 fatty acids causes polymerization, weak oxidation stability, and low calorific value, even when cannot efficiently utilize the algaederived bio-oil for transportation fuel. Considering this, Fang et al [69] researched the facile conversion of palmitic acid to hexadecane catalyzed by the bifunctional PTA@ PdCu@Fe III -MOF-5, which was prepared by immobilizing phosphotungstic acid into the MOF structure. e explored catalyst demonstrates an enhanced acidity and efficiently facilitates palmitic acid for hexadecane with relatively high selectivity.…”
Section: Upgrading Of Other Biobased Compoundsmentioning
confidence: 99%